The Urine-culturing Cascade: Variation in Nursing Home Urine Culturing and Association With Antibiotic Use and Clostridiodes difficile Infection. (14th June 2019) - Brown, Kevin Antoine; Daneman, Nick; Schwartz, Kevin L; Langford, Bradley; McGeer, Allison; Quirk, Jacquelyn; Diong, Christina; Garber, Gary
Abstract: Background: Rates of antibiotic use vary widely across nursing homes and cannot be explained by resident characteristics. Antibiotic prescribing for a presumed urinary tract infection is often preceded by inappropriate urine culturing. We examined nursing home urine-culturing practices and their association with antibiotic use. Methods: We conducted a longitudinal, multilevel, retrospective cohort study based on quarterly nursing home assessments between April 2014 and January 2017 in 591 nursing homes and covering >90% of nursing home residents in Ontario, Canada. Nursing home urine culturing was measured as the proportion of residents with a urine culture in the prior 14 days. Outcomes included receipt of any systemic antibiotic and any urinary antibiotic (eg, nitrofurantoin, trimethoprim/sulfonamides, ciprofloxacin) in the 30 days after the assessment and Clostridiodes difficile infection in the 90 days after the assessment. Adjusted Poisson regression models accounted for 14 resident covariates. Results: A total of 131 218 residents in 591 nursing homes were included; 7.9% of resident assessments had a urine culture in the prior 14 days; this proportion was highly variable across the 591 nursing homes (10th percentile = 3.4%, 90th percentile = 14.3%). Before and after adjusting for 14 resident characteristics, nursing home urine culturing predicted total antibiotic use (adjusted risk ratio [RR] per doubling of urine culturing, 1.21; 95% confidence interval [CI], 1.18–1.23), urinary antibiotic use (RR, 1.33; 95% CI, 1.28–1.38), and C. difficile infection (incidence rate ratio, 1.18; 95% CI, 1.07–1.31). Conclusions: Nursing homes have highly divergent urine culturing rates; this variability is associated with higher antibiotic use and rates of C. difficile infection. Abstract : Urine-culturing rates varied dramatically across 591 nursing homes in Ontario, despite adjustment for resident characteristics. High nursing home urine culturing rates were associated with increased total antibiotic use, Clostridiodes difficile infection, and 30-day mortality.